View Church Catholic To Life Political Indonesian Society As Relevance Gaudium et Spess 73-76 - Gea, Mawarni; Lase, Yusuf Nataeli; Zebua, David Arron Fesa (Universitas Sanata Dharma, 2026)
Life of Indonesian society still colored by conflict, such as corruption, nepotism, discrimination, SARA politics, and money politics . The purpose of writing is to provide an understanding to every Catholic believer, especially the Indonesian people, to use their reason and conscience in realizing common welfare ( bonum commune ), through politics. The writing method used is a literature review with various references found in books, journals, and documents. Humans are a social society in the image of God and have the dignity of life as a special gift from God. The Catholic Church is present to teach moral principles that must be upheld by the state in carrying out its duties. The state is expected to prioritize justice, truth and common welfare ( bonum commune ) in its policies . Politics is not just a matter of power and policy, but a calling to serve others in creating a better world. Thus, politics becomes a positive means of building a just, peaceful and prosperous society in accordance with the moral and ethical teachings of religion.